PERSON SPEECH BEHAVIOR MARKERS IN EXTREME SITUATION (ACCORDING TO SUAKHILI LITERARY SOURCE) - Fattakhova, Aida R.; Biyanova, Evgeniya A. (Gênero & Direito, 2019)
An extreme situation implies an active influence on the psychological-emotional state of a person, which is expressed in tension, agitation, aggression and other manifestations of temperament, deviated from the generally accepted norms of behavior. In artistic texts, the representation of a person’s speech behavior in an extreme (conflict) situation is realized through the Swahili language means that mark a conflict communicative act. In this article, based on the material of the Swahiliazy novel "The World is Chaos" by E. Kesilahabi, an attempt is made to study the markers that reveal the speech behavior of a conflict communicative act participants. Phonetics-graphic, grammatical and lexical markers are distinguished, the most frequent of them are identified (the use of a wide range of interjections, the highlighting of a phrase with an exclamation point, syntactic repetitions, the use of invective vocabulary, etc.). The authors come to the conclusion that the simultaneous implementation of these markers is observed in the dicthemes of conflict communicative acts to a greater extent. The results of the research can be used for further developments in the field of linguistics, ethnic-linguistics, psycholinguistics, grammar, translation studies, etc